Bioinformatics and the Cell Modern Computational Approaches in Genomics, Proteomics and Transcriptomics - Xia, Xuhua (Springer International Publishing, 2018)
This second edition integrates the more technical and mathematical aspects of bioinformatics with concrete examples of their application to current research problems in molecular and cellular biology. This broad, unified approach is made possible, in large part, by the very wide scope of Dr. Xia's own research experience. The integration of genomics, proteomics and transcriptomics into a single volume makes this book required reading for anyone entering the new and emerging field of Systems Biology.